2014
DOI: 10.1016/j.bbamcr.2014.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Structural determinants for the ouabain-stimulated increase in Na–K ATPase activity

Abstract: Recent studies suggest that at low concentrations, ouabain increases Na-K ATPase and NHE1 activity and activates the Src signaling cascade in proximal tubule cells. Our laboratory demonstrated that low concentrations of ouabain increase blood pressure in rats. We hypothesize that ouabain-induced increase in blood pressure and Na-K ATPase activity requires NHE1 activity and association. To test this hypothesis we treated rats with ouabain (1μgkg body wt(-1)day(-1)) for 9days in the presence or absence of the NH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Interestingly, total internal reflection fluorescence microscopy (TIRFM) showed that deletion of the N-terminal CBD of Na C /K C ATPase resulted in the failure of trafficking of Na C /K C ATPase a-subunit and NHE1 to the basolateral membranes. Mutations in the scaffold domain or the activity domain of NHE1 prevented the induction of the increase in Na C /K C ATPase activity by ouabain (Khundmiri et al 2014). These data indicate that an association between Na C /K C ATPase and NHE1 triggered by low-dose ouabain is essential for Src activation and the increase in sodium reabsorption in the proximal tubular cells (Fig.…”
Section: Atpase Activitymentioning
confidence: 50%
“…Interestingly, total internal reflection fluorescence microscopy (TIRFM) showed that deletion of the N-terminal CBD of Na C /K C ATPase resulted in the failure of trafficking of Na C /K C ATPase a-subunit and NHE1 to the basolateral membranes. Mutations in the scaffold domain or the activity domain of NHE1 prevented the induction of the increase in Na C /K C ATPase activity by ouabain (Khundmiri et al 2014). These data indicate that an association between Na C /K C ATPase and NHE1 triggered by low-dose ouabain is essential for Src activation and the increase in sodium reabsorption in the proximal tubular cells (Fig.…”
Section: Atpase Activitymentioning
confidence: 50%
“…Cells were washed three times with serum-free low-phosphate (0.1 mM phosphate) MEM without phenol red and incubated in 2 ml low-phosphate MEM. Total internal reflection fluorescence (TIRF) microscopy was performed in a humidified incubation chamber maintained at 37°C and 5% CO 2 as previously described (17).…”
Section: Methodsmentioning
confidence: 99%
“…The vehicle group received PBS intraperitoneally and the ouabain group received 1 μg/kg body weight/day ouabain for 9 days. Blood was collected from carotid artery and serum was separated after measuring blood pressure (blood pressure data was reported previously)[3,6]. …”
Section: Materials and Experimental Methodsmentioning
confidence: 99%
“…We and others have demonstrated that cardioglycosides like ouabain exert a biphasic effect on NKA activity, low concentrations stimulating and higher concentrations inhibiting the activity of NKA [25]. Our laboratory has demonstrated that ouabain-mediated stimulation of NKA involves an NHE1 dependent activation of a signaling complex that includes EGFR, Src kinase, ERK, and Akt [3,6]. We have also demonstrated that low concentrations of ouabain increase blood pressure in Sprague Dawley rats in an NHE1 dependent manner [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation